300 LITERATURE CASE SERIES REVIEW ON LANDIOLOL IN ACUTE DECOMPENSATED HEART FAILURE SECONDARY TO TACHYARRHYTHMIAS. (15th December 2022) - Cereda, Alberto; Laricchia, Alessandra; Marini, Claudia; Franchina, Gabriele; Conconi, Barbara; Lucreziotti, Stefano
Abstract: Introduction: Landiolol is a recently innovated ultra-short-acting beta-blocker. Landiolol is the only beta-blocker with a specific dose recommendation for patients with cardiac dysfunction and acute atrial fibrillation (Class I recommendation according to the ESC guidelines). Landiolol has a shorter elimination half-life than any other beta-blocker, and it can be administered safely to patients with various tachyarrhythmias. The short duration of action and titratability of landiolol makes it ideal for use in critically ill patients. Purpose of the Study: Review the case reports in the literature on the administration of landiolol in critically ill patients with acute decompensated heart failure (ADHF) secondary to tachyarrhythmias. Methods: 11 case reports of ADHF secondary to tachyarrhythmias were identified. Personal, clinical and humoral data were collected. The heart rate and systolic pressure values in the time before and after the administration of Landiolol were plotted in a summary graph. Results: The mean age of the 11 patients was 55 years old with high proBNP values at admission. The etiological diagnosis of heart failure was heterogeneous but tachyarrhythmia was the trigger event in all patients. Patients were critically ill with a mean EF of 26 ± 16% and an initial shock index of 1.4 ±0.5. Landiolol administered together with other antiarrhythmic drugs (amiodarone in 4/11 patients), epinephrine/norepinephrine (9/11) and levosimendan (4/11) favoured heart rate lowering and an increase in systolic blood pressure.At discharge, 4/11 had improved EF, in 10/11 sinus rhythm was restored, and all patients recovered hemodynamic stability without adverse events related to Landiolol (Figure 1). Conclusion: In this case series review, Landiolol was a useful strategy in patients with ADHF refractory to conventional therapy by facilitating rate/rhythm control, limiting the toxicity of inotropic drugs and improving the hemodynamic profile. Figure 1